Pengaruh Model Cooperative Integrated Reading and Composition Terhadap Kemampuan Membaca Pemahaman Siswa Kelas V SDN Ponjanan Timur 1 - Ningtias, Indri Ardi Ayu; Citrawati, Tyasmiarni (Yayasan Arrahman Nahdlatul Wathan, 2024)
This study aims to determine the influence of the cooperative integrated reading and composition model on the reading ability of the students class V SDN Ponjanan Timur 1. This study is a quantitative study of the experimental type, the design used is pre-experimental design in the form of one group pretest posttest design. The population surveyed was all V-grade students. As for sampling using non-probability samplings using saturated sampler techniques. The samples surveyed in this study were all V class students with a total of 24 students. Data is gathered through observations and tests. The results of this study show that the coopeartive model of integrated reading and composition has an influence on the reading ability of 5th grade students of SDN East Ponjanan 1. Based on the calculation of the hypothesis test using the paired simple t-test obtained thitung of 10,863 and ttable of 2,074 values of significance of 0,000. Based on the test criteria if thitung > ttable then Ha is accepted and H0 is rejected. It can be stated thitung value > ttabel is 10,863 > 2,074 so that Ha is received and H0 is refused, if the result of Sig.2(tailed) < 0,05 or 0,000 < 0,05, then H0 has been refused and Ha has been accepted. Based on this, it can be concluded that there is a significant influence of cooperative model integrated reading and composition on the ability to read understanding of students of V grade SDN Ponjanan Timur 1.